Dos sindicatos dos padres à Igreja Viva: Igreja Católica e questões sociais do campo no Brejo paraibano da década de 1960 - Silva, Waléria Kássia Martins da (2020)
During the 1960’s, in Brejo paraibano, union associations and rural workers movements associated to the Catholic Church flourished, demonstrating the historical complexity of this religious institution in social, political, cultural and symbolic dimensions. With a strongly anticommunist perspective and promoting harmony between social classes, as guided by its Social Doctrine, the Catholic Church of Paraíba in the early 1960's organized a formation of rural workers' unions in order to make the Brejo micro-region something like a “containment belt” of the “subversive” advance of the Peasant Leagues in the rural areas of the state. These unions, popularly known as "Unions of the Fathers", acted in favor of the working class always within the order. With the 1964 coup, instituted with the support of the Catholic Church itself, these unions went through an emptying process, since it considered that the work to counter communism had ended after the so-called “revolution”. However, over the following years, part of the Catholic Church underwent changes in its assessment of the social reality of that period and promoted changes in the way it intervened in the region. In order to promote struggles for the acquisition of rights, part of the Church reoriented its action in Brejo with the development of a new conception expressed in the “Igreja Viva” movement. Based on the analysis of primary sources, such as newspapers, minutes of union meetings, union letters, books from the parishes and documents produced by the lay movements of the Catholic Church of Paraíba, especially from Brejo itself, and in dialogue with the specialized bibliography, and with the theoretical support of Antonio Gramsci and Pierre Bourdieu, we seek, in this Master's Dissertation, to contribute to the process of producing knowledge about the Social and Political History of Brazil, especially the History of Paraíba, through the analysis of the relationships established by this traditional ecclesiastical institution with the rural working class of the mid-20th century.